Kepuasan Nasabah PT. Bank Rakyat Indonesia Unit Tapan Cabang Painan Dilihat dari Kualitas Layanan Customer Service - Doni Marlius; Izet Putriani (JURNAL PUNDI, 2019)
This research was conducted on customers at PT. BRI Painan Branch Tapan Unit. The purpose of this study was to examine the effect of physical evidence, reliability, response, assurance and empathy on customer satisfaction. This type of research is quantitative research. The object of this research is PT. BRI Painan Branch Tapan Unit. The sampling method used is incidental sampling and the data is processed by multiple linear regression analysis, test the validity, reliability and hypothesis testing with the t test and test f. The results of the physical evidence research t count> t table so that the physical evidence has an effect on customer satisfaction, the results of reliability research t count> t table so that reliability has an effect on customer satisfaction, the results of the research t count> t table so that the responses affect the customer satisfaction, the results of the research guarantee t count> t table so that shows that collateral affects customer satisfaction, the results of empirical research t count > t table so that it shows empathy affects customer satisfaction and the results of physical evidence, reliability, responsiveness, assurance, and empathy. f count > f table so that it shows physical evidence, reliability, responsiveness, assurance, and empathy that have a significant effect on customer satisfaction.